At dark, I become loathsome - LaRocca, Eric (Blackstone Publishing, 2025)
"A single line of text, glowing in the darkness of the internet. Written by Ashley Lutin, who has often thought the same--and worse--in the years since his wife died and his young son disappeared. But the peace of the grave is not for him--it's for those he can help. Ashley has constructed a peculiar ritual for those whose desire to die is at war with their yearning to live a better life. Struggling to overcome his own endless grief, one night Ashley finds connection with Jinx--a potential candidate for Ashley's next ritual--who spins a tale both revolting and fascinating. Thus begins a relationship that traps the two men in an ever-tightening spiral of painful revelations, where long-hidden secrets are dragged, kicking and screaming, into the light. Only through pain can we find healing. Only through death can we find new life."--Amazon.